2022
DOI: 10.1111/joor.13320
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for alterations to dynamic quantitative sensory tests in patients with chronic temporomandibular myalgia: A systematic review of observational studies with meta‐analysis

Abstract: Background Conflicting results exist between somatosensory profiles of patients with temporomandibular myalgia (TMDm). The objective of this review was to examine whether adults with TMDm show altered responses to dynamic quantitative sensory tests compared with healthy controls. Methods We searched five electronic databases for studies, excluding those without suitable controls or where TMDm was associated with confounding non‐musculoskeletal disorders. Risk of bias was assessed with the SIGN case‐control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Thus, TMD-M is rarely accompanied by clinical signs and histopathologic evidence of injury or inflammation (Ettlin et al, 2021). Therefore, some studies (Kosek et al, 2016) have classified TMD-M as nociplastic pain (Cayrol et al, 2022). Despite these debatable points, there is an agreement that TMD-M leads to sensitization of nociceptive and non-nociceptive trigeminal ganglia (TG) sensory neurons innervating the masticatory muscles, leading to increase signal input into the central nervous system (Fitzcharles et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TMD-M is rarely accompanied by clinical signs and histopathologic evidence of injury or inflammation (Ettlin et al, 2021). Therefore, some studies (Kosek et al, 2016) have classified TMD-M as nociplastic pain (Cayrol et al, 2022). Despite these debatable points, there is an agreement that TMD-M leads to sensitization of nociceptive and non-nociceptive trigeminal ganglia (TG) sensory neurons innervating the masticatory muscles, leading to increase signal input into the central nervous system (Fitzcharles et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…2,5,21,25,32,41 Through quantitative sensory testing, studies have shown that individuals with TMD tend to have lower pressure pain thresholds and experience more pain in response to repeated nociceptive stimuli (ie, temporal summation) at extratrigeminally innervated sites. 12,21 Besides, a recent prospective study showed that pressure pain thresholds throughout the body decrease after the onset of TMD and return to normal after TMD remission. 42 These findings suggest alterations in trigeminal and extratrigeminal nociceptive processing, but are hardly indicative of the pathophysiology of TMD.…”
Section: Introductionmentioning
confidence: 99%
“…42 These findings suggest alterations in trigeminal and extratrigeminal nociceptive processing, but are hardly indicative of the pathophysiology of TMD. 4,10 Moreover, the sensitivity to stimuli is not found to be globally altered in patients with TMD 12,16,21 ; therefore, studies on specific physiological mechanisms are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TMDM is often not accompanied by such clinical signs as histopathologic evidence of injury or inflammation 7 . Therefore, some studies 8 have classified TMDM as nociplastic pain 9 . Despite these debatable points, there is an agreement that TMDM leads to sensitization of nociceptive and maybe non-nociceptive trigeminal ganglia (TG) sensory neurons innervating the masticatory muscles, leading to increase signal input into the central nervous system 10 .…”
mentioning
confidence: 99%